Ictiofauna de los humedales del río San Pedro, Balancán, Tabasco, México - Alfonso Castillo-Domínguez; Everardo Barba Macías; Alberto de Jesús Navarrete; Rocío Rodiles-Hernández; María de Lourdes Jiménez Badillo (Revista de Biología Tropical, 2011)
Los humedales de San Pedro sostienen redes tróficas del sistema fluvial debido a la alta disponibilidad de hábitats y a sus variaciones espacio-temporales. En esta investigación se estudió la composición, densidad y biomasa de la ictiofauna de los humedales; se capturaron 1 049 organismos de 25 especies, dos son exóticas: Oreochromis niloticus y Parachromis managuense. Con 23 especies capturadas en el sitio I, 17 en el II y 14 en el III. En la época de secas se obtuvo mayor riqueza con 21 especies, lluvias con 17 y cinco en nortes. La mayor densidad se mostró en el sitio II (0.23ind./m²), seguido de los sitios I y III (0.12, 0.12ind./m²). La mayor biomasa fue en secas (8.30g/m²), seguida de lluvias (2.1g/m²) y por último nortes (0.01g/m²). La mayor densidad se mostró en secas (0.43ind./m²) y la mínima en nortes (0.023ind./m²). Las especies dominantes en densidad según el diagrama Olmstead-Tukey fueron: Petenia splendida, Vieja heterospila, Vieja synspila, Dorosoma petenense y Astyanax aeneus. Por lo tanto, existieron diferencias significativas en los parámetros ecológicos y ambientales. Al considerar la variación en la riqueza podemos concluir que los humedales del río San Pedro, es un sistema donde la composición de la ictiofauna responde a las fluctuaciones espaciales y temporales. Ichthyofauna from wetlands of San Pedro, Balancán, Tabasco, México. San Pedro River’s wetlands sustain trophic nets in the fluvial system, due to the high habitat availability, and space and temporal variations. In order to describe the relationship between environmental parameters and ichthyofauna, this study evaluated fish assemblages composition, distribution, abundance, density, biomass, richness species, diversity and equitability in the wetlands. Sampling considered three different sites and climatic seasons (dry, rainy and cold fronts). The physical and chemical parameters considered were dissolved oxygen, temperature, pH, water transparency and the depth. Fishes were caught with a shrimp net, after six minutes towings and were identified afterwards. A total of 1 049 organisms of 25 fish species were caught, two of which were exotic species: Oreochromis niloticus and Parachromis managuense. A total of 23 species were found at site I (with the highest density 0.23ind./m²), 17 at site II (0.23ind./m²) and 14 at site III (0.12ind./m²). The dry season had the highest species number with 21 species, followed by the rainy season with 17 species, and the cold season with five species. Similarly, the highest biomass (8.30g/m²) was found in dry season, followed by the rainy (2.16g/m²) and the cold seasons (0.03g/m²). Considering seasons, highest density was found during the dry (0.436ind./m²), followed by the rainy (0.213ind./m²) and the cold (0.023ind./m²) seasons. The dominant density species during the study period, according to the quadrants graphic of Olmstead-Tukey were: Petenia splendida, Vieja heterospila, Vieja synspila, Dorosoma petenense and Astyanax aeneus. There were significant differences in the species richness among sites. Temperature, depth and transparency showed differences among the seasons. The canonical correspondence analysis indicated that fish distribution was governed by environmental parameters during all seasons. In terms of fish abundance and composition, environmental parameters play an important role showing spatial and temporal differences in the ecosystem, this could be explained with the fact that most of young fishes have a movement behavior to the wetlands, searching refuge and feed during the dry season. Considering the diversity indexes variation, it may be concluded that San Pedro River’s wetlands correspond to a system where the ichthyofauna composition fluctuates spatial and seasonally. Rev. Biol. Trop. 59 (2): 693-708. Epub 2011 June 01.